The evaluation of body composition and anthropometric measurements of males aged 18-25 years, based on the regularity of physical exercise - Aksoy, Aziz; Selen, Halime (Progress in Nutrition, 2018)
There were 200 participants in total, on a voluntary basis in the study. Of these participants, 100 were male students aged 18-25 years who exercised regularly and vigorously, and 100 were male aged 18-25 years who did not participate in any physical activity. The measurements of BMI, body fat composition, hip-to-waist ratio, and skinfolds measured at nine different anatomical areas of their bodies (pectoral, biceps, triceps, subscapular, abdominal, suprailiac, thigh, midaxillary and the medial part of the leg) using skinfold caliper were recorded in the Excel format. It was determined that there was a significant difference (p<0.05) between the BMI of those who exercised regularly and of those who did not, and that there were significant differences (p<0.05) between muscle weights, hip-to-waist ratio, body fat composition, total body water, and basal metabolic rates of the participants who exercised regularly and of those who did not. It was determined that the total body water was increased in the subjects who exercised regularly due to increased muscle weight and mass, their hip-to-waist and body fat ratios were lower, and basal metabolic rates were higher when compared to the non-exercisers. It was also determined that there were significant differences (p<0.05) between the two groups regarding of skinfold caliper measurements at nine different areas. When the data from the study, which is the first to include nine different anatomical regions, was evaluated, it was concluded that the sedentary lifestyle influences the onset of obesity and it can be partially treated with physical activity.